Kinetics of high temperature oxidation of chromium rich HfC reinforced cobalt based alloys. (February 2014) - Conrath, E.; Berthod, P.
<x content-type="archive" xml:space="preserve">Abstract</x> Mostly known to improve the high temperature oxidation resistance of superalloys, hafnium may also form carbides. Several per cents of Hf allow developing a dense carbide network to mechanically strengthen alloys. Here, the high temperature oxidation behaviour of three HfC containing cobalt alloys was characterised at all steps of a thermogravimetry test: heating, isothermal stage and cooling, compared with two Co–Cr–C model alloys. The five alloys were heated in synthetic air, maintained at 1200°C during 50 h and then cooled. The mass gains were plotted versus time or according to (m×dm/dt = Kp–m×Kv) to specify the isothermal kinetic constants, or versus temperature to determine how oxidation acts during heating and oxide spallation occurs during cooling. Compared to the ternary alloys, the oxidation of the HfC reinforced alloys starts earlier but leads to lower mass gains during heating, the isothermal oxidation is faster and oxide spallation occurs later.